The grand regulator : the miseducation of Nova Scotia's teachers, 1838-1997 - Perry, George D. (McGill-Queen's University Press, 2013)
Schools of education with utilitarian goals and strict standardization - often called "Normal Schools" - have been widely criticized by both the academy and the general public. In a story that resonates across Canada, The Grand Regulator examines an educational system that failed to inspire great teachers and produce imaginative, thinking citizens. Drawing on an array of archival materials, government publications, and firsthand accounts with former Normal School students, George Perry provides a rich reconstruction of the intellectual, social, economic, and political foundations of teacher education in Nova Scotia, and the methodological preoccupations that have hampered its subsequent development. He shows how a supposed science of education based on child psychology, in concert with the province's regulation of public schooling, justified low expectations for the education of most children and how standardized training programs deemphasized teachers' general liberal education and intellectual curiosity. The most complete study of Canadian teacher education to date, The Grand Regulator presents an analysis of perennial issues regarding the improvement of education that continue to concern us, and illuminates ways of raising the level of instruction in our present-day schools.